Evaluasi Penerapan Sistem Pemerintahan Berbasis Elektronik (SPBE) di Dinas Komunikasi dan Informasi Kota Padang - Hidayatullah, Santy; Adha, Sisri Nadia; Olivia, Regina; Hidayahtunnisa, Refa; Hanoselina, Yulia; ., Yuliarti (Jurnal Ekonomi dan Bisnis Digital, 2026)
The development of information and communication technology has driven digital transformation in government administration to enhance efficiency, transparency, and the quality of public services. One of the Indonesian government's efforts to achieve this is through the implementation of the Electronic- Based Government System (SPBE). This study aims to evaluate the effectiveness of SPBE implementation at the Department of Communication and Informatics of Padang City and to identify the factors influencing its success in supporting governance. This research is based on e-government theory, policy evaluation concepts, New Public Management (NPM), and the design-reality gap concept. The study employs a qualitative approach with a descriptive method. Data were collected through observation and semi-structured interviews conducted on April 8, 2026. The results show that SPBE implementation has positively contributed to improving administrative efficiency, strengthening internal coordination, and enhancing the quality of digital-based public services. However, the implementation is not yet optimal due to several challenges, including lack of system integration among regional agencies, limited human resource capacity, low digital literacy among the community, and system security issues. Therefore, strengthening system integration, improving human resource capacity, and conducting continuous evaluation are necessary to optimize SPBE implementation in achieving effective and sustainable governance.